Enzyme superoxide dismutase in grain of barley and malt - Natálie Belcrediová; Jaroslava Ehrenbergerová; Pavla Havlová (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2006)
The aim of the work was modification of superoxide dismutase enzyme (SOD, EC 1.15.1.1) activity analysis in barley grain and identical malts with using of the Ransod set. This set from company Randox were used for enzyme determination in blood samples. This method employs xanthine and xanthine oxidase to generate superoxide radicals, which react with tetrazolium chloride to form a red formazan dye. SOD is classified as natural antioxidants and enzyme plays a significant role at detoxication of products of molecular oxygen degradation. The largest rate of SOD occurs in embryo of barley grain. Its presence in barley grain and malt thus inhibits rancidity of grain during storage and undesirable beer flavour. The line Wabet x Washonubet (in grain-104,93 and malt 152,42 U/g dry matter) and the variety Annabell (104,65 a 147,21 U/g dry matter) had the highest activity of SOD in grain and malt of barley while the lowest activity was measured in the line KM 1910 (73,15 a 88,16 U/g dry matter) and variety Tolar (74,34 a 96,44 U/g dry matter).